Roles of the organizational psychologist in the face of continuous change - Solf Zárate, Arturo (2025)
Currently, work organizations require constant changes in response to an environment that demands it. It is proposed that Organizational Psychologists could provide professional services to facilitate such changes from the perspective of three methodologies: Design Thinking (PDD), Employee Experience Design (DEx), and Appreciative Inquiry (IA), and two strategies for the development of adaptive resources of workers: Promoting Learning and providing Coaching and Psychological Counseling. The document is aimed primarily at students interested in Organizational Psychology, and those who manage diplomas and masters in this area. In addition, information is included that could be useful to Educational Psychologists.